KAUM MINORITAS MUSLIM DI BARAT: Tantangan dan Masa Depan - Damanhuri, Damanhuri (Analisis: Jurnal Studi Keislaman, 2012)
The Muslim minorities in the West face various challenges originally come from within Muslim communities as well as Western’s negative attitudes upon them. Unfortunately, those challenges often lead Western Muslims to take two different attitudes with similar danger: preaching isolationist stance that considers everything seemed more or less characteristic  of the West in manners or style as dangerous and they contrives to forbid or avoid it as much as possible; or campaigning assimilation, in its literal sense—complete  adaptation to the Western way of life. This book deals with the challenges of Western Muslims and the theoretical-practical  efforts they must undertake  for their better future as well. Tariq Ramadan  calls all Western  Muslims  to reread their Islamic classical texts as well as ground them in Western socio- political context. In so doing, Tariq Ramadan contends that, through fresh interpretations of universal Islamic principles, the path towards an authentic integration is open for Western Muslims.